Multi-omics analysis reveals neutrophil heterogeneity and key molecular drivers in sepsis-associated acute kidney injury - Cheng, Tianle; Xu, Yong; Liu, Ziwei; Wang, Yanchen; Zhang, Ze; Huang, Wenlin (Frontiers in Immunology, 2025)
Sepsis-associated acute kidney injury is a critical condition driven by immune dysregulation, particularly involving neutrophils, yet their heterogeneity and molecular contributions remain underexplored. This study employed a multi-omics approach, integrating single-cell and bulk RNA sequencing from 21 sepsis samples and Escherichia coli-induced sepsis datasets, alongside bioinformatics, machine learning, and experimental validation in a rat model and human peripheral blood. We identified four neutrophil subtypes—pro-inflammatory, anti-inflammatory, mature, and immature—revealing a significant increase in pro-inflammatory neutrophils in sepsis (40.53% versus 4.19% in controls) and a decrease in anti-inflammatory neutrophils (18.43% versus 27.04%). Four hub genes, peptidyl arginine deiminase 4, caspase 4, complement receptor 1, and mitogen-activated protein kinase 14, were pinpointed as key drivers, with peptidyl arginine deiminase 4 mediating neutrophil extracellular trap formation and exacerbating renal damage. In a rat model, peptidyl arginine deiminase 4 knockdown reduced trap formation and alleviated kidney injury (p-value less than 0.01). Human samples confirmed elevated gene expression in sepsis (p-value less than 0.05). These findings highlight neutrophil heterogeneity and molecular mechanisms in sepsis, with potential implications for sepsis-associated acute kidney injury (SAKI), proposing novel biomarkers and therapeutic targets for precision medicine.